Global miRNA expression profiling of domestic cat livers following acute Toxoplasma gondii infection - Cong, Wei; Zhang, Xiao-Xuan; He, Jun-Jun; Li, Fa-Cai; Elsheikha, Hany M.; Zhu, Xing-Quan (Impact Journals, 2017)
Although microRNAs (miRNAs) play an important role in liver homeostasis, the extent to which they can be altered by Toxoplasma gondii infection is unknown. Here, we utilized small RNA sequencing and bioinformatic analyses to characterize miRNA expression profiles in the liver of domestic cats at 7 days after oral infection with T. gondii (Type II) strain. A total of 384 miRNAs were identified and 82 were differentially expressed, of which 33 were up-regulated and 49 down-regulated. Also, 5690 predicted host gene targets for the differentially expressed miRNAs were identified using the bioinformatic algorithm miRanda. Gene ontology analysis revealed that the predicted gene targets of the dysregulated miRNAs were significantly enriched in apoptosis. Kyoto Encyclopedia of Genes and Genomes analysis showed that the predicted gene targets were involved in several pathways, including acute myeloid leukemia, central carbon metabolism in cancer, choline metabolism in cancer, estrogen signaling pathway, fatty acid degradation, lysosome, nucleotide excision repair, progesterone-mediated oocyte maturation, and VEGF signaling pathway. The expression level of 6 upregulated miRNAs (mmu-miR-21a-5p, mmu-miR-20a-5p, mmu-miR-17-5p, mmu-miR-30e-3p, mmu-miR-142a-3p, and mmu-miR-106b-3p) was confirmed by stem-loop quantitative reverse transcription PCR, which yielded results consistent with the sequencing data. These findings expand our understanding of the regulatory mechanisms of miRNAs underlying T. gondii pathogenesis and contribute new database information on cat miRNAs, opening a new perspective on the prevention and treatment of T. gondii infection.